Impact of age and gender on tumor related prognosis in gastrointestinal stromal tumors (GIST) - Kramer, Klaus; Knippschild, Uwe; Mayer, Benjamin; Boegelspacher, Kira; Spatz, Hanno; Henne-Bruns, Doris; Agaimy, Abbas; Schwab, Matthias; Schmieder, Michael (BMC Cancer, 2015)
Risk classification and prediction of prognosis in GIST is still a matter of debate. Data on the impact of age and gender as potential confounding factors are limited. Therefore we comprehensively investigated age and gender as independent risk factors for GIST.Two independent patient cohorts (cohort I, n = 87 [<50 years]; cohort II, n = 125 [>=50 years]) were extracted from the multicentre Ulmer GIST registry including a total of 659 GIST patients retrospectively collected in 18 collaborative German oncological centers. Based on demographic and clinicopathological parameters and a median follow-up time of 4.3 years (range 0.56; 21.33) disease-specific-survival (DSS), disease-free-survival (DFS) and overall survival (OS) were calculated.GIST patients older than fifty years showed significantly worse DSS compared to younger patients (p = 0.021; HR = 0.307, 95% CI [0.113; 0.834]). DSS was significantly more favorable in younger female GIST patients compared with elderly females (p = 0.008). Female gender resulted again in better prognosis in younger patients (p = 0.033).Patient age (<50 years) and female gender were significantly associated with a more favourable prognosis in GIST. Extended studies are warranted to confirm our clinical results and to elucidate underlying pathophysiological mechanisms.
EVALuna2:6716